Abacs Márton és Zalányi László vitája és a hit artikulusai - Vilmos József KOLUMBÁN (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Dispute between Márton Abacs and Laszló Zalányi and the Principles of Faith.